Prognostic factors to predict the survival in patients with advanced gastric cancer who receive later‐line nivolumab monotherapy—The Asahikawa Gastric Cancer Cohort Study (AGCC). (29th November 2021) - Tanaka, Kazuyuki; Tanabe, Hiroki; Sato, Hiroki; Ishikawa, Chisato; Goto, Mitsuru; Yanagida, Naoyuki; Akabane, Hiromitsu; Yokohama, Shiro; Hasegawa, Kimiharu; Kitano, Yohei; Sugiyama, Yuya; Uehara, Kyoko; et al.
Abstract: Background: Chemotherapy for advanced gastric cancer is recommended in the guidelines; however, later‐line treatment remains controversial. Since immune checkpoint inhibitors have been used for the treatment of various malignancies, trials have been performed for gastric cancer. A phase 3 trial indicated the survival benefit of nivolumab monotherapy for gastric cancer patients treated with prior chemotherapy regimens. Patients and methods: A regional cohort study was undertaken to determine the real‐world data of nivolumab treatment for patients with advanced or recurrent gastric cancer. The patients were enrolled for 2 years from October 2017 to October 2019 and were prospectively followed for 1 year to examine the overall survival (OS). The patient characteristics were analyzed in a multivariate analysis and a nomogram to predict the probability of survival was generated. Results: In total, 70 patients who received nivolumab as ≥third‐line chemotherapy were included in the Asahikawa Gastric Cancer Cohort. The median OS was 7.5 (95% CI, 4.8–10.2) months and the response rate was 18.6%. Diffuse type classification, bone metastasis, high neutrophil/lymphocyte ratio, and high CRP were associated with poor OS/prognosis in the multivariate analysis. A nomogram was developed based on these clinical parameters and the concordance index was 0.80 (95% CI, 0.68–0.91). The responders were aged and were frequently diagnosed with intestinal type gastric cancer, including patients with a HER2‐positive status (27.3%) or microsatellite instability‐high (27.3%) status. Conclusions: The regional cohort study of nivolumab monotherapy for gastric cancer patients revealed prognostic factors and a nomogram was developed that could predict the probability of survival. Abstract : Development and validation of the nomogram. The nomogram of different risk factors for survival at 7.5 months in gastric cancer patients treated with nivolumab.